SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DI PT BANDAR UDARA INTERNASIONAL JAWA BARAT - Hidayattulloh, Asep Manurul; Whydiantoro (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
This study discusses the implementation of Occupational Safety and Health Management System (SMK3) at PT Bandar Udara Internasional Jawa Barat. The research aims to describe the policies, procedures, and effectiveness of SMK3 implementation in the airport area. A qualitative method was used through observation, interviews with safety officers, and analysis of company documents. The findings show that PT BIJB has implemented several K3 policies including restricted area entry, personal protective equipment usage, prohibition of smoking, alcohol and drugs, as well as procedures for hazard identification, first aid, fire prevention, safety inspections, training, safety communication, safety signage, and investigations. The results indicate that although most of the SMK3 requirements have been met, improvements are still needed in some facilities and preventive measures.